Pragmatic competence of children with autism spectrum disorder. Impact of theory of mind, verbal working memory, ADHD symptoms, and structural language. Issue 2 (3rd April 2019) - Baixauli-Fortea, Inmaculada; Miranda Casas, Ana; Berenguer-Forner, Carmen; Colomer-Diago, Carla; Roselló-Miranda, Belén
ABSTRACT: The primary aim of this study is to increase the existing knowledge about the pragmatic skills of children with autism spectrum disorders (ASD). Specifically, the study has two objectives. The first is to provide a profile of characteristics based on The Children's Communication Checklist (CCC-2) pragmatics scales (inappropriate initiation, stereotyped language, use of context, nonverbal communication, and general pragmatics) and narrative task indicators. To this end, children with ASD will be compared to children with typical development (TD), controlling the effects of sex and structural language (speech, syntax, semantics, coherence). The second objective is to analyze whether theory of mind (ToM), verbal working memory, ADHD symptoms, and structural language can predict pragmatic competence in children with ASD without intellectual disability (ID). The results showed worse performance in the group with ASD on the majority of the pragmatic aspects evaluated. In addition, the application of ToM skills and structural language were significant predictors of the pragmatic skills of the children with ASD. These findings reinforce the importance of focusing intervention programs on mentalist abilities through experiences in real social scenarios, along with strengthening structural language components.